Relaxed parameter conditions for chemotactic collapse in logistic-type parabolic–elliptic Keller–Segel systems - Black, Tobias; Fuest, Mario; Lankeit, Johannes (Zeitschrift für angewandte Mathematik und Physik)
Keywords: Applied Mathematics; General Physics and Astronomy; General Mathematics

Prescribed signal concentration on the boundary: Weak solvability in a chemotaxis-Stokes system with proliferation - Black, Tobias; Wu, Chunyan (Zeitschrift für angewandte Mathematik und Physik)
Keywords: Applied Mathematics; General Physics and Astronomy; General Mathematics

A composite consisting of intermetallic Ni3Fe and nitrogen-doped carbon for electrocatalytic water oxidation: The effect of increased pyridinic nitrogen dopant - Liu, Dan; Zhai, Haichao; Hu, Jie; Pan, Ying; Xu, Gengsheng; Zhu, Chuhong; Yuan, Yupeng (Ceramics International)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Process Chemistry and Technology; Ceramics and Composites; Electronic; Optical and Magnetic Materials

Robust ferroelectric polarization retention in harsh environments through engineered domain wall pinning - Zhang, Dawei; Sando, Daniel; Pan, Ying; Sharma, Pankaj; Seidel, Jan (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Carbon-Based Metal-Free Electrocatalysts: Past, Present, and Future - Zhai, Qingfeng; Pan, Ying; Dai, Liming (Accounts of Materials Research)
Keywords: Materials Chemistry; Polymers and Plastics; Materials Science (miscellaneous); Chemical Engineering (miscellaneous)

Strain‐Engineered Nano‐Ferroelectrics for High‐Efficiency Piezocatalytic Overall Water Splitting - Su, Ran; Wang, Zhipeng; Zhu, Lina; Pan, Ying; Zhang, Dawei; Wen, Hui; Luo, Zheng‐Dong; Li, Linglong; Li, Fa‐tang; Wu, Ming; He, Liqiang; Sharma, Pankaj; et al. (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

A universal electrochemical activation enabling lattice oxygen activation in nickel-based catalyst for efficient water oxidation - Hu, Jie; Jiang, Daochuan; Weng, Zhaoyue; Pan, Ying; Li, Zhongjun; Du, Haiwei; Yuan, Yupeng (Chemical Engineering Journal)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; Environmental Chemistry; General Chemistry

Anisotropic Ion Migration and Electronic Conduction in van der Waals Ferroelectric CuInP2S6 - Zhang, Dawei; Luo, Zheng-Dong; Yao, Yin; Schoenherr, Peggy; Sha, Chuhan; Pan, Ying; Sharma, Pankaj; Alexe, Marin; Seidel, Jan (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Cascaded dual-loop organic Rankine cycle with alkanes and low global warming potential refrigerants as working fluids - Abbas, Wameedh Khider Abbas; Vrabec, Jadran (Energy Conversion and Management)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Der Einfluss der Besteuerung auf Managementanreize und die Nutzung von Bonusbanken - Dyck, Daniel (Junior Management Science)

Editorial: Schmalenbach IMPULSE: Will etwas in Bewegung setzen - Asenkerschbaumer, Stefan; Sureth-Sloane, Caren (Schmalenbach IMPULSE)

CoViD-19 als Katalysator für die digitale Professionalisierung angehender Lehrpersonen? - Schwabl, Franziska; Vogelsang, Christoph (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Die CoViD-19-Pandemie ab Frühjahr 2020 und die pandemiebedingten Kontaktbeschränkungen hatten erhebliche Auswirkungen auf die studienbegleitenden Praxisphasen im Lehramtsstudium. Studierende, die ihr Praxissemester im Sommersemester 2020 absolvierten, waren in der Folge erheblich von Einschränkungen sowohl während der universitären Begleitveranstaltungen als auch in den Praxisschulen betroffen. Durch die überwiegende Umstellung von Präsenzformaten zu digitalem Lehren und Lernen auf Distanz ist die Annahme naheliegend, dass Studierende vermehrt die Möglichkeit hatten, Erfahrungen mit digitalen Lernformaten zu machen. Anhand einer Sekundäranalyse der Befragung einer Kohorte von Praxissemesterstudierenden der Universität Paderborn (N=362) kann allerdings gezeigt werden, dass der erwartete Möglichkeitsraum für eine digitale Professionalisierung keineswegs ausgeschöpft bzw. überhaupt genutzt wurde. Vielmehr zeigte sich, dass angehende Lehrpersonen digitale Medien vor allem dann in den eigenen Unterricht einbetten, wenn diese in der mentoriellen Begleitung thematisiert wurde oder während Hospitationen beobachtet werden konnte. Zudem deuten die Analysen an, dass ungünstige Professionalisierungsbedingungen an den Praxisschulen nur bedingt durch die universitären Anteile der Praxisphasen aufgefangen werden konnten. Für die Gestaltung der universitären Lehrpersonenausbildung ergibt sich daher u. a. die Notwendigkeit einer intensiveren Kooperation zwischen den verschiedenen Akteuren der drei Phasen der Lehrpersonenbildung.

Selbstreguliertes Lernen im berufsschulischen Übergangssystem - Daniel-Söltenfuß, Desiree; Schwabl, Franziska (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

Selbstreguliertes Lernen fördern - Lernen auf Distanz ermöglichen - Schwabl, Franziska; Daniel-Söltenfuß, Desiree (berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)

Effectiveness of health-oriented leadership interventions for improving health and wellbeing of employees: a systematic review - Dannheim, Indra; Ludwig-Walz, Helena; Buyken, Anette; Grimm, Valerie; Kroke, Anja (Journal of Public Health)
Abstract Aim To identify and summarize the evidence for the effect of health-oriented leadership interventions on health and well-being outcomes at the employee level following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (Moher et al. 2009). Subject and Methods A systematic search of relevant studies was conducted in multiple databases. Randomized controlled trials (RCTs), cluster-randomized controlled trials (cRCTs) and controlled before–after studies (CBAs) were included based on the following criteria: interventions that addressed supervisors, to raise awareness for the importance of health issues, teach mindfulness practices for conscious awareness, reduce stress and promote resources at the level of individual behavior, and evaluated the effect on at least one outcome of psychomental stress, absenteeism and well-being on the employee level. Results Of 6126 publications retrieved, ten studies were identified for analysis. Significant effects of leadership training were reported on exhaustion tendency, self-reported sickness absence, work-related sickness absence and job satisfaction in studies comparing health-oriented training programs to no intervention. Studies comparing health-oriented leadership training to other training did not report significant effects. Risk of bias was judged to be high in seven studies and unclear in three studies. Conclusion Evidence for the effectiveness of health-oriented leadership interventions on employees’ stress, absenteeism or well-being is judged to be low, clearly indicating the need for more and higher-quality research.
Keywords: Public Health; Environmental and Occupational Health

Zur Einführung in Kapitel 10 und 11 - Grimminger-Seidensticker, Elke; Brandl-Bredenbeck, Hans Peter; Gerlach, Erin; Krieger, Claus (Sportpädagogik. Eine Grundlegend)

Forschungsmethodische Zugänge - Grimminger-Seidensticker, Elke; Krieger, Claus (Sportpädagogik. Eine Grundlegung)

Des arbitrages éthiques face aux injonctions à la pratique physique dans les programmes de promotion de la santé : le cas des familles populaires en Europe - Grimminger-Seidensticker, Elke; Vieille Marchiset, G.; Knobé, S.; Aceti, M. (SociologieS.)

Der historische Muhammad in der islamischen Theologie. Zur Kriterienfrage in der Leben-Muhammad-Forschung - Ghaffar, Zishan

Bright Electrically Controllable Quantum‐Dot‐Molecule Devices Fabricated by In Situ Electron‐Beam Lithography - Schall, Johannes; Deconinck, Marielle; Bart, Nikolai; Florian, Matthias; Helversen, Martin; Dangel, Christian; Schmidt, Ronny; Bremer, Lucas; Bopp, Frederik; Hüllen, Isabell; Gies, Christopher; Reuter, Dirk; et al. (Advanced Quantum Technologies)
Keywords: Electrical and Electronic Engineering; Computational Theory and Mathematics; Condensed Matter Physics; Mathematical Physics; Nuclear and High Energy Physics; Electronic; Optical and Magnetic Materials; Statistical and Nonlinear Physics